Per-object systematics using deep-learned calibration - Kasieczka, Gregor; Luchmann, Michel; Otterpohl, Florian; Plehn, Tilman (SciPost physics, 2020)
SciPost Journals Publication Detail SciPost Phys. 9, 089 (2020) Per-object systematics using deep-learned calibration